2019
DOI: 10.1002/jbm.a.36657
|View full text |Cite
|
Sign up to set email alerts
|

Zinc‐oxide nanoparticles act catalytically and synergistically with nitric oxide donors to enhance antimicrobial efficacy

Abstract: The development of infection‐resistant materials is of substantial importance as seen with an increase in antibiotic resistance. In this project, the nitric oxide (NO)‐releasing polymer has an added topcoat of zinc oxide nanoparticle (ZnO‐NP) to improve NO‐release and match the endogenous NO flux (0.5–4 × 10−10 mol cm−2 min−1). The ZnO‐NP is incorporated to act as a catalyst and provide the additional benefit of acting synergistically with NO as an antimicrobial agent. The ZnO‐NP topcoat is applied on a polyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Previous studies have shown polymeric medical devices with NO‐releasing capacity for the use of endotracheal tubes, insulin cannula, catheters, extracorporeal circulation, and so forth 17,49,52 . Results obtained in this study align with previously published articles that emphasize the compatibility of SNAP‐loaded polymers for biomedical applications 59,66 . Cell compatibility studies confirmed >70% cell survival rate with all samples (Figure 8).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have shown polymeric medical devices with NO‐releasing capacity for the use of endotracheal tubes, insulin cannula, catheters, extracorporeal circulation, and so forth 17,49,52 . Results obtained in this study align with previously published articles that emphasize the compatibility of SNAP‐loaded polymers for biomedical applications 59,66 . Cell compatibility studies confirmed >70% cell survival rate with all samples (Figure 8).…”
Section: Discussionsupporting
confidence: 88%
“…3 d) as well as from covalently attached NO donors through various biodegradation mechanisms [125 , 127] . Additionally, NO-releasing scaffolds and nanoparticles have been designed to target organs and tissues to deliver payloads following stimuli-response to differences in oxidation environment or the presence of catalytic metal ions [127] , [128] , [129] , [130] , [131] . Through rational design approaches, NO-releasing formulations could be developed to target specific viral disease states.…”
Section: Survey Of No-based Antiviral Therapiesmentioning
confidence: 99%
“…Therefore, increasing the release amount of NO is completely necessary. Researchers have designed catalytic release systems by combining SNAP with catalysts such as platinum nanoparticles [115], copper nanoparticles (Cu-NPs) [116], Cu 1.6 S nanoparticle [117], zinc oxide nanoparticles [118], ebselen [119], or selenium [120], to achieve a large amount release of NO. Handa et al top-coated 1, 3, and 5 wt % of Cu-NPs to SNAP doped Carbosil films to fabricate Cu-SNAP films.…”
Section: No Releasing Polymeric Materials For Antibacterial Applicmentioning
confidence: 99%